2012
DOI: 10.1111/aji.12014
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal Serpin A1 and A3 Levels in HIV Highly Exposed Sero‐Negative Women are Affected by the Menstrual Cycle and Hormonal Contraceptives but are Independent of Epidemiological Confounders

Abstract: This study shows the relationship of serpins to the menstrual cycle and hormonal contraceptives, as well as their independence to epidemiological sexual confounders. This information provides a broader understanding of innate components of the mucosal immune system in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 34 publications
2
13
0
1
Order By: Relevance
“…Overexpressed proteins in these individuals included many serpins (31), several of which were also overexpressed in the follicular phase in our study, as determined by both proteomic and genomic analyses, consistent with earlier findings (32). Serpins are reported to possess anti-inflammatory properties (33) and are important players in mucosal defense against HIV (32), especially in the eclipse phase (27). However, it is noteworthy that not all serine protease inhibitors we tested in this study (including SLPI and trappin-2) showed significantly different expression in the two menstrual phases.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Overexpressed proteins in these individuals included many serpins (31), several of which were also overexpressed in the follicular phase in our study, as determined by both proteomic and genomic analyses, consistent with earlier findings (32). Serpins are reported to possess anti-inflammatory properties (33) and are important players in mucosal defense against HIV (32), especially in the eclipse phase (27). However, it is noteworthy that not all serine protease inhibitors we tested in this study (including SLPI and trappin-2) showed significantly different expression in the two menstrual phases.…”
Section: Discussionsupporting
confidence: 92%
“…It is intriguing to note that apoliprotein A-I (Apo A-I) was one of the abundantly expressed proteins (31) in the cervicovaginal mucosa of highly exposed seronegative (HESN) sex workers. Overexpressed proteins in these individuals included many serpins (31), several of which were also overexpressed in the follicular phase in our study, as determined by both proteomic and genomic analyses, consistent with earlier findings (32). Serpins are reported to possess anti-inflammatory properties (33) and are important players in mucosal defense against HIV (32), especially in the eclipse phase (27).…”
Section: Discussionsupporting
confidence: 90%
“…Others, using a proteomic approach, have shown a significant difference in serpin A1 levels in the CVL based on menstrual cycle phase among highly exposed seronegative women. 63 In addition, proteomic data support that CV epithelial adhesion proteins and antiproteases were reduced, and leukocyte recruitment and extravasation proteins are elevated in the CVL of healthy HIV-negative women during the LUT phase, which may support reduced CV epithelial defenses in the LUT phase. 64 The two clinical studies reported here have several strengths, foremost being that we screened participants to exclude factors such as RTIs and other medical comorbidities, which may confound endpoints when using explants or samples obtained from a wide variety of donors undergoing indicated surgery.…”
Section: No Differences In Vaginal Ph or Nugent Score Between Fol Andmentioning
confidence: 83%
“…In contrast, anti-inflammatory factors such as antiproteases have been associated with reduced acquisition among highly exposed sex workers (18,23). Several of these antiviral factors have shown a relationship with the menstrual cycle and the corresponding ovarian hormones dominant during each phase, including an elevation of serpins during the follicular phase (24), and a reduction of SLPI and defensins during the ovulatory/early luteal phase (25,26). Although there is a body of evidence supporting an association between progesterone and menstrual cycle phase with altered host mucosal innate immunity, a comprehensive analysis has never been performed and represents a major gap in knowledge.…”
mentioning
confidence: 99%